Recruitment of Complement Factor H-Like Protein 1 Promotes Intracellular Invasion by Group A Streptococci - Pandiripally, Vinod (American Society for Microbiology, 2003)
Numerous microbial pathogens exploit complement regulatory proteins such as factor H (FH) and factor H-like protein 1 (FHL-1) for immune evasion. Fba is an FHL-1 and FH binding protein expressed on the surface of the human pathogenic bacterium, Streptococcus pyogenes, a common agent of pharyngeal, skin, and soft-tissue infections. In the present study, we demonstrate that Fba and FHL-1 work in concert to promote invasion of epithelial cells by S. pyogenes. Fba fragments were expressed as recombinant proteins and assayed for binding of FHL-1 and FH by Western blotting, enzyme-linked immunosorbent assay, and surface plasmon resonance. A binding site for FHL-1 and FH was localized to the N-terminal half of Fba, a region predicted to contain a coiled-coil domain. Deletion of this coiled-coil domain greatly reduced FHL-1 and FH binding. PepSpot analyses identified a 16-amino-acid segment of Fba which overlaps the coiled-coil domain that binds both FHL-1 and FH. To localize the Fba binding site in FHL-1 and FH, surface plasmon resonance was used to assess the interactions between the streptococcal protein and a series of recombinant FH deletion constructs. The Fba binding site was localized to short consensus repeat 7 (SCR 7), a domain common to FHL-1 and FH. SCR 7 contains a heparin binding site, and heparin was found to inhibit FHL-1 binding to Fba. FHL-1 promoted entry of Fba(+) group A streptococci into epithelial cells in a dose-dependent manner but did not affect invasion by an isogenic fba mutant. To our knowledge, this is the first report of a bacterial pathogen exploiting a soluble complement regulatory protein for entry into host cells.